Differential blood count as triage tool in evaluation of pelvic masses. Issue 5 (2nd June 2020) - Cramer, Daniel W; Benjamin IV, William J; Vitonis, Allison F; Berkowitz, Ross; Goodman, Annekathryn; Matulonis, Ursula
Abstract : Objective: Triaging patients with presumptive ovarian cancer to the appropriate specialist may improve survival. Therefore, there is increasing interest in complementary diagnostic markers to the standard serum CA125. In patients with pelvic masses, we examined the ability of epidemiologic variables and preoperative differential blood counts to improve detection of ovarian cancer over CA125 alone. Methods: From pathology reports, patients were classified as having: epithelial ovarian cancer (n=743), including fallopian tube and primary peritoneal cancer, non-epithelial ovarian cancers (n=46), non-ovarian cancers (n=122), or benign disease (1, 129). From women with epithelial ovarian cancer, we excluded those who received prior neoadjuvant chemotherapy (n=19). Women were also excluded if they did not have a serum CA125 or complete blood count measured within 180 days prior to surgery (n=1099) or did not have both tests within 90 days of each other (n=13). Categorizing patients by menopausal status, we calculated Pearson correlations between differential counts or ratios and CA125, and used t tests to identity univariate predictors of malignancy and stepwise logistic regression and likelihood ratio tests to create models best distinguishing epithelial ovarian cancer from benign disease. Results: 337 women with epithelial ovarian cancer and 365 with benign disease were included in the analysis. Compared with cancers, women with benign disease had lower average: age, 52.5 versus 58.4 years (p<0.0001); serum CA125, 20 versus 239 U/mL (p<0.0001), neutrophil-to-lymphocyte ratio, 2.4 versus 3.5 (p<0.0001); and platelet-to-lymphocyte ratio, 158 versus 222 (p<0.0001); but greater average body mass index, 28.5 versus 26.8 kg/m 2 (p=0.004), and lymphocyte-to-monocyte ratio, 5.6 versus 3.9 (p<0.0001). Correlations between counts and ratios and serum CA125 were seen in both epithelial ovarian cancer and benign disease groups and differed by menopausal status. In premenopausal women, a multivariate model including serum CA125, smoking, family history, lymphocytes, and monocytes performed similarly to the model with lymphocyte-to-monocyte ratio replacing counts. In postmenopausal women, a model including body mass index, parity, monocytes, and basophils performed similarly to the model replacing counts with platelet-to-lymphocyte ratio and lymphocyte-to-monocyte ratio. Models including epidemiologic variables and either counts or ratios were better at fitting data than models with serum CA125 and menopausal status alone. A single model applying to all women overstated performance for premenopausal women and understated performance for postmenopausal women. Conclusions: Epidemiologic variables and differential counts or ratios better distinguished between benign and malignant disease when compared with serum CA125 alone using separate models for pre- and postmenopausal women.